Comparison of mechanical properties of 3D printer resins for occlusal splints using different models of 3D printers - Seidler, Arthur Simoes; de Melo, Lucas Simino; Limirio, João Pedro Justino de Oliveira [UNESP]; Pesqueira, Aldieris Alves [UNESP]; Hilgert, Leandro Augusto; de Medeiros, Rodrigo Antonio (Medicina Oral, S.L., 2024)
Background: Considering the development of new 3D printing technologies that use different printing techniques, further studies must be conducted to evaluate the impact of different printing systems on the mechanical properties of 3D-printed materials. This study aimed to evaluate the mechanical properties of 3D-printed materials for occlusal devices using different 3D printers and printing layer thicknesses. Material and Methods: Ninety rectangular samples were manufactured and divided into nine groups according to the 3D printer model they were printed on (AnyCubic Mono X, Elegoo Mars 2, or FlashForge Hunter) and the layer thickness (20, 50, or 100 µm) and were subjected to superficial microhardness, flexural resistance, and elasticity modulus tests. The results were analyzed using two-way analysis of variance and Tukey's statistical tests, with a significance level of 5%. Results: The type of 3D printer significantly affected superficial microhardness (p = 0.007). Flexural strength showed a significant interaction between the 3D printer and layer thickness (p = 0.005), with both factors independently influencing flexural strength (printer: p< 0.001, layer thickness: p< 0.001). Elasticity modulus was significantly influenced by the 3D printer type (p< 0.001) and the interaction between both factors (p = 0.004). The AnyCubic Mono X 3D printer with a 20 µm layer thickness exhibited more consistent mechanical properties than the other printers. Conclusions: Variations in printing systems and layer thicknesses can impact the mechanical properties of 3D-printed materials. Key words:CAD-CAM. Bruxism. Temporomandibular disorders. Mechanical tests; 3-D printing.Care Team.